Discovering Regalos: A Case Study of Saint Anne's Middle School - (:unkn) unknown (My University, 2013)
Saint Anne's Middle School is a Catholic, bilingual, bicultural, middle school for girls that participates in the Milwaukee Parental School Choice Program. This case study explored reading and language arts as experienced in the school through the lens of a school library media specialist. The students’ social, emotional, and intellectual needs appeared to be met at the school for the most part. The school also exhibited best practices for teaching reading at the middle school level to bilingual students. However, to improve reading, the school would want to consider changing the school’s focus from reading comprehension to reading engagement so that students become lifelong readers. In addition, as schools begin to roll out the new educational framework known as the Common Core, which will change how librarians and teachers present reading, and standardized tests assess reading, it is essential that more time be dedicated to exploring point-of-view in informational texts. Finally, because the students tend to score lower on vocabulary than comprehension in reading assessments, increasing the use of free-reading books to introduce vocabulary may provide further opportunities for students to improve on standardized test scores while teaching a valuable lifelong skill. In sum, even a strong school can improve on reading and language arts instruction, and this project shows ways that teachers and librarians can change their thinking to be ready to implement Common Core and still achieve reading engagement.
Keywords: Bilingual Education; Catholic Schools; Library Media; Literacy; Reading; Urban Middle Schools